Transfer printing method of catalyst layer

By applying the catalytic layer on the substrate layer and pasting the support layer to form a composite transfer film, the problem of low tensile strength of the substrate film is solved, the transfer quality and film strength of the catalytic layer are improved, and efficient catalytic layer transfer is achieved.

CN119764464AInactive Publication Date: 2025-04-04SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410180873.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-18
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing catalytic layer transfer technology, the tensile strength of the substrate film is low, resulting in a large pressure required during transfer, and it is prone to deformation after heat treatment, which affects the uniform drying and transfer quality of the catalytic layer.

Method used

A catalytic layer is prepared by coating the front of the substrate layer, and a support layer is pasted on the back of the substrate to form a composite transfer film. Then a proton exchange film is stacked between the composite transfer films and heat-pressed transfer is performed.

Benefits of technology

The strength of the transfer film is improved, the deformation of the catalytic layer is reduced, and the coating preparation effect and transfer quality of the catalytic layer are ensured. At the same time, the compatibility is good and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764464A_ABST
    Figure CN119764464A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a transfer printing method of a catalyst layer, and relates to the technical field of catalyst layer preparation. The transfer printing method of the catalyst layer comprises the following steps that the catalyst layer is prepared on the front face of the base material layer in a coating mode, then the supporting layer is pasted on the back face of the base material layer, and a composite transfer printing film is formed; the proton exchange membrane is stacked between the two layers of composite transfer printing membranes, and the catalyst layer of each layer of composite transfer printing membrane is close to the proton exchange membrane to form a transfer printing structure; carrying out hot pressing on the transfer printing structure, so that the catalyst layer is transferred to the proton exchange membrane; and separating the base material layer, the supporting layer and the proton exchange membrane. According to the transfer printing method of the catalyst layer, the coating preparation effect of the catalyst layer can be guaranteed, the strength of the transfer printing film can be improved, and deformation of the catalyst layer after transfer printing is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of catalytic layer preparation, and in particular to a method for transferring a catalytic layer. Background Art

[0002] The CCM (catalyst coated membrane) of a proton exchange membrane fuel cell or a proton exchange membrane water electrolyzer includes a proton exchange membrane and a catalytic layer located on both sides of the proton exchange membrane. The catalytic layers on both sides serve as the cathode and the anode, respectively. The CCM can be prepared by transfer printing. When preparing by transfer printing, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene terephthalate, polybutylene terephthalate and other substrate films are mostly used as transfer films. Such substrate films often have the characteristics of high temperature resistance and easy peeling of the coating, but their tensile strength is low and they are easily stretched and deformed after being heated. They can only be transferred by flat hot pressing. In order to ensure the bonding strength between the catalytic layer and the proton exchange membrane, the transfer requires a large pressure, but the upper limit of the pressure of flat transfer is low, which cannot meet the high pressure requirements during transfer. Moreover, this type of substrate film has low tensile strength and is easily stretched and deformed after being heated, which will lead to poor quality of roll-to-roll hot roller transfer, inability to accurately control the coating shape of the catalytic layer, and difficulty in achieving intermittent coating transfer.

[0003] In order to improve the tensile strength of the substrate film, the prior art will composite a layer of supporting film on the back of the substrate film to form a composite transfer film for coating and transferring the catalytic layer. However, if this composite transfer film is to meet the tensile strength requirements, the thickness of the supporting layer needs to be increased. Compared with a single-layer substrate film, when coating the catalytic layer on a thicker composite transfer film, it is difficult for heat to penetrate the transfer film to dry the catalytic layer from the inside out, which can easily lead to uneven drying of the catalytic layer and cause the catalytic layer to crack. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide a transfer method for a catalytic layer, which can ensure the coating preparation effect of the catalytic layer, and can also improve the strength of the transfer film and reduce the deformation of the catalytic layer after transfer.

[0005] The present application provides a method for transferring a catalytic layer, which comprises the following steps:

[0006] A catalytic layer is coated on the front side of the substrate layer, and a supporting layer is adhered to the back side of the substrate layer to form a composite transfer film;

[0007] The proton exchange membrane is stacked between two layers of the composite transfer membrane, and the catalytic layer of each layer of the composite transfer membrane is close to the proton exchange membrane to form a transfer structure;

[0008] Hot pressing the transfer structure to transfer the catalytic layer onto the proton exchange membrane;

[0009] The substrate layer, the support layer and the proton exchange membrane are separated.

[0010] In the above implementation process, the catalytic layer is first coated on the substrate layer, which does not affect the coating operation, and can also avoid the problem of cracking of the catalytic layer due to uneven drying when the catalytic layer is coated on a thick composite transfer film, which can ensure the coating preparation effect of the catalytic layer; after the catalytic layer is coated, the support layer is adhered to the back of the substrate layer coated with the catalytic layer to form a composite transfer film, and then the transfer is performed, which can improve the strength of the transfer film, reduce the deformation of the catalytic layer after transfer, and improve the transfer quality; and by adhering the support layer on the substrate layer, the tensile strength of the substrate layer can be improved to achieve roll-to-roll hot roller transfer, and the transfer coating size can be guaranteed to be accurate, without affecting the coating process, without the need to develop a new coating process, good compatibility and low cost. The transfer method of the present application is widely applicable. Different support layers can be used to meet the different tensile strength requirements during transfer: support layers of different materials and thicknesses can be freely selected according to the tensile strength required by the transfer equipment and transfer conditions to achieve the tensile strength required for transfer, and multiple conditions can be adapted without adjusting the coating parameters.

[0011] In a possible implementation, the support layer is adhered to the back side of the substrate layer by using a heat-sensitive adhesive.

[0012] In the above implementation process, the thermosensitive adhesive has a lower viscosity at a lower temperature and a higher viscosity at a higher temperature. The thermosensitive adhesive is used to adhere the substrate layer and the support layer together for easy recycling. After the transfer is completed, the support layer is peeled off from the substrate layer through cooling treatment to achieve the reuse of the substrate layer and the support layer, saving costs and avoiding the poor recyclability of conventional composite transfer films, which are easy to curl after the transfer is completed, resulting in difficulty in preparing the catalytic layer again and high costs.

[0013] In a possible implementation, a heat-sensitive adhesive is coated on the front side of the support layer to form a heat-sensitive adhesive layer, and then the front side of the support layer is adhered to the back side of the substrate layer.

[0014] In a possible implementation, the thickness of the heat-sensitive adhesive layer is 30-60 μm.

[0015] In the above implementation process, a certain thickness of the heat-sensitive adhesive layer facilitates the bonding of the support layer and the substrate layer together and their separation by cooling, and can also reduce the impact on the quality of hot pressing transfer.

[0016] In a possible implementation, when forming the transfer structure, the same end of the support layer of the two layers of the composite transfer membrane is extended out and adhered to the proton exchange membrane.

[0017] In the above implementation process, after the composite transfer membranes and proton exchange membranes on both sides are aligned before transfer, the front support layer and the proton exchange membrane are pasted and positioned, which can ensure the relative position of the rear layers is accurate and improve the transfer quality.

[0018] In a possible implementation, the protruding ends of the two support layers are adhered together by the heat-sensitive adhesive to form the transfer structure.

[0019] In the above implementation process, the protruding ends of the two support layers are adhered to the proton exchange membrane by using a thermosensitive adhesive, so that the adhered layers can be easily separated after the transfer is completed.

[0020] In a possible implementation, the catalytic layer is an intermittent coating formed by intermittent coating, and the protruding ends of the two support layers are adhered together to align the two catalytic layers.

[0021] In the above implementation process, the front end of the support layer is pasted and positioned to ensure that the relative positions of the layers at the rear end are accurately aligned during transfer, and the alignment accuracy of the intermittent transfer of the two catalyst layers can be ensured.

[0022] In a possible implementation, the support layer extends 20-500 mm relative to the substrate layer, the proton exchange membrane extends 10-100 mm relative to the substrate layer, and the proton exchange membrane extends less than the support layer.

[0023] In the above implementation process, the same end of the support layer of the two-layer composite transfer membrane is made to extend a longer part, and the proton exchange membrane extends a shorter part. The support layer and the proton exchange membrane on both sides can be adhered together by using the adhesive layer of the support layer, and at the same time, accurate alignment during transfer can be ensured to improve the transfer quality.

[0024] In a possible implementation, the hot pressing temperature is 120-200° C., the pressure is 1-8 MPa, and the tension is 10-50N.

[0025] In the above implementation process, certain hot pressing conditions ensure the bonding strength between the catalyst layer and the proton exchange membrane, while the transfer efficiency is high.

[0026] In a possible implementation, the material of the substrate layer includes at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene terephthalate, and polybutylene terephthalate, and the thickness of the substrate layer is 30-150 μm;

[0027] And / or, the material of the support layer includes at least one of polyester, polycarbonate, triacetyl cellulose, polytetrafluoroethylene fabric, cellophane, polyphenylene sulfide, polysulfone, polyether sulfone, and polypropylene, and the thickness of the support layer is 60-160 μm;

[0028] And / or, the thickness of the catalytic layer is 10-30 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A schematic diagram of a transfer structure provided in an embodiment of the present application;

[0031] Figure 2 for Figure 1 A top view of

[0032] Figure 3 Schematic diagram of the structure of the CCM layer obtained after transfer.

[0033] Icon: 111 - first catalytic layer; 112 - first substrate layer; 113 - first supporting layer; 120 - proton exchange membrane; 131 - second catalytic layer; 132 - second substrate layer; 133 - second supporting layer. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0036] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0037] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0038] In the description of this application, it should be noted that the terms "upper", "lower", "horizontal", "inner", "outer", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the application is usually placed when in use. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this application. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0039] In addition, the term "horizontal" does not mean that the component is required to be absolutely horizontal or suspended, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0040] In the description of this application, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0041] Please see Figures 1 to 3 The present invention provides a method for transferring a catalyst layer, which comprises the following steps:

[0042] S1. A catalytic layer is coated on the front side of the substrate layer, and a supporting layer is adhered on the back side of the substrate layer to form a composite transfer film.

[0043] In some embodiments of the present application, the material of the substrate layer includes at least one of polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polyethylene terephthalate (PET), and polybutylene terephthalate (PBT), and the thickness of the substrate layer is 30-150 μm. The material and thickness of the substrate layer can be selected according to actual needs, mainly to meet the needs of coating and preparing the catalyst. Exemplarily, the thickness of the substrate layer is 30 μm, 50 μm, 70 μm, 100 μm, 130 μm, 150 μm, or an intermediate value between any two of the above values.

[0044] In some embodiments of the present application, the support layer includes materials such as polyester, polycarbonate, triacetyl cellulose, polytetrafluoroethylene fabric, cellophane, polyphenylene sulfide, polysulfone, polyether sulfone, polypropylene, etc., and the thickness of the support layer is 60-160 μm. The material and thickness of the support layer can be selected according to actual needs, mainly to meet the tensile strength requirements during hot pressing. Exemplarily, the thickness of the support layer is 60 μm, 70 μm, 100 μm, 130 μm, 150 μm, 160 μm or an intermediate value between any two of the above values. Furthermore, for the case where the transfer tension strength is large, the transfer quality can be ensured by increasing the thickness of the support layer to increase the overall tensile strength.

[0045] In some embodiments of the present application, the thickness of the catalytic layer is 10-30 μm. Exemplarily, the thickness of the catalytic layer is 10 μm, 20 μm, 30 μm, or an intermediate value between any two of the above values.

[0046] In some embodiments of the present application, the catalytic layer includes a catalyst and an ionomer, and the catalyst is selected from at least one of a Pt / C catalyst, a Pt alloy / C catalyst, an iridium oxide, and a ruthenium oxide.

[0047] In some embodiments of the present application, the support layer is adhered to the back side of the substrate layer by a pressure-sensitive adhesive. Optionally, the pressure-sensitive adhesive is a polyacrylate pressure-sensitive adhesive, a polyvinyl ether pressure-sensitive adhesive or a silicone pressure-sensitive adhesive.

[0048] In some embodiments of the present application, the support layer is adhered to the back side of the substrate layer by a heat-sensitive adhesive; optionally, the heat-sensitive adhesive is a peelable heat-sensitive adhesive having a lower viscosity at a lower temperature and a higher viscosity at a higher temperature, such as the heat-sensitive adhesive disclosed in patent JP2003138237A or JP5512143B2.

[0049] As an implementation mode, a heat-sensitive adhesive is coated on the front side of the support layer to form a heat-sensitive adhesive layer, and then the front side of the support layer is adhered to the back side of the substrate layer; optionally, the thickness of the heat-sensitive adhesive layer is 30-60 μm.

[0050] In the embodiment of the present application, the first catalyst layer 111 corresponding to the anode is coated on the first substrate layer 112, and the first support layer 113 is adhered to form a first composite transfer film, and the second catalyst layer 131 corresponding to the cathode is coated on the second substrate layer 132, and the second support layer 133 is adhered to form a second composite transfer film. The first catalyst layer 111 and the second catalyst layer 131 usually have different compositions and different thicknesses, which are determined according to product design requirements.

[0051] The “front side” and “back side” in the embodiments of the present application are used to distinguish two opposite surfaces of the film layer, and do not limit the orientation of the film layer after stacking.

[0052] S2. The proton exchange membrane 120 is stacked between two layers of composite transfer membranes, and the catalyst layer of each layer of the composite transfer membrane is close to the proton exchange membrane 120 layer, so as to form a transfer structure.

[0053] In the embodiment of the present application, a transfer structure of first support layer 113 - first substrate layer 112 - first catalyst layer 111 - proton exchange membrane 120 - second catalyst layer 131 - second substrate layer 132 - second support layer 133 is formed.

[0054] In some embodiments of the present application, when forming the transfer structure, the same end of the support layer of the two layers of the composite transfer membrane is extended and adhered to the proton exchange membrane 120. As an implementation method, the extended ends of the two layers of the support layer are adhered together by a peelable thermosensitive adhesive to form the transfer structure, and specifically, the adhesion can be achieved by previously coating the front surface of the support layer with a thermosensitive adhesive to form a thermosensitive adhesive layer.

[0055] In the embodiment of the present application, a certain distance is reserved at the front end of the coil, and the layers are stacked in sequence, the reserved support layers are pasted together to be positioned, and the extended ends of the two support layers are pasted together with the proton exchange membrane 120 by a heat-sensitive adhesive.

[0056] As an embodiment, the width of each layer is 400-600mm, the protruding length of the support layer relative to the substrate layer is 20-500mm, the proton exchange membrane 120 protrudes relative to the substrate layer 10mm-100mm, and the protruding length of the proton exchange membrane 120 is smaller than the protruding length of the support layer. By setting the protruding length, the protruding end of the support layer can be adhered to the protruding end of the proton exchange membrane 120 by adhesive, but will not adhere to the substrate layer and the catalyst layer.

[0057] In the embodiment of the present application, the catalytic layer is an intermittent coating formed by intermittent coating, and the protruding ends of the two support layers are glued together to align the two catalytic layers. Figure 2As shown, a support layer with a certain distance is reserved at the front end of the coil without pasting the substrate layer. After the coatings on both sides of the first sheet are aligned with the proton exchange membrane 120 before transfer, the front support layer is pasted to ensure the relative position of each coating at the rear end is accurate.

[0058] S3 . Hot-pressing the transfer structure to transfer the catalyst layer onto the proton exchange membrane 120 .

[0059] In some embodiments of the present application, the temperature of hot pressing is 120-200°C, the pressure is 1-8Mpa, and the tension is 10-50N, where the tension refers to the tension to which the first composite transfer film and the second composite transfer film are subjected in the transfer device, respectively. The process conditions of hot pressing can be selected according to actual needs to improve the transfer quality and efficiency. In the embodiments of the present application, the transfer device is a conventional device in the art, and may include components such as an unwinding roller, a hot pressing transfer roller, and a winding roller, and its detailed structure will not be repeated here.

[0060] S4, separating the substrate layer, the support layer and the proton exchange membrane 120 to obtain a CCM layer.

[0061] In the present application, the CCM layer (whose structure is as follows) is separated. Figure 3 As shown), a first composite transfer membrane (excluding the first catalytic layer 111), and a second composite transfer membrane (excluding the second catalytic layer 131), and the CCM layer is rolled up to obtain a product.

[0062] In some embodiments of the present application, during separation, the ends of the support layer and the ends of the proton exchange membrane that are stuck together can be cut off first, so that the first composite transfer membrane (excluding the first catalytic layer 111), the transfer membrane and the head ends of the second composite transfer membrane (excluding the second catalytic layer 131) are separated.

[0063] In some embodiments of the present application, when a peelable thermal adhesive is used, when separating, the end of the support layer and the end of the proton exchange membrane that are stuck together can be first cooled and torn apart, so that the first composite transfer membrane (excluding the first catalytic layer 111), the transfer membrane and the head end of the second composite transfer membrane (excluding the second catalytic layer 131) are separated.

[0064] In some embodiments of the present application, when a peelable thermal adhesive is used, the first composite transfer film and the second composite transfer film are cooled after the transfer is completed, and the viscosity of the thermal adhesive decreases after cooling, so that the first substrate layer 112 and the first support layer 113, and the second substrate layer 132 and the second support layer 133 can be torn and separated for reuse.

[0065] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0066] Example 1

[0067] This embodiment provides a CCM layer, which is prepared according to the following transfer method:

[0068] S1. The first catalytic layer 111 corresponding to the anode is prepared by coating the front side of the first substrate layer 112. The first catalytic layer 111 is an intermittent coating formed by intermittent coating. The thickness of the first catalytic layer 111 is 10 μm. An adhesive layer is formed by coating the front side of the first support layer 113. The front side of the first support layer 113 is then adhered to the back side of the first substrate layer 112 to form a first composite transfer film.

[0069] A second catalytic layer 131 corresponding to the cathode is prepared by coating the front side of the second substrate layer 132. The thickness of the second catalytic layer 131 is 18 μm. The second catalytic layer 131 is an intermittent coating formed by intermittent coating. An adhesive layer is formed by coating the front side of the second support layer 133. The front side of the second support layer 133 is then adhered to the back side of the second substrate layer 132 to form a second composite transfer film.

[0070] The substrate layer (first substrate layer 112, second substrate layer 132) is made of polytetrafluoroethylene with a thickness of 60 μm, the support layer (first support layer 113, second support layer 133) is made of PET with a thickness of 60 μm, and the adhesive layer is made of silicone pressure-sensitive adhesive with a thickness of 40 μm. The width of the substrate layer (first substrate layer 112, second substrate layer 132) and the support layer (first support layer 113, second support layer 133) is 500 mm, and the catalytic layer (first catalytic layer 111, second catalytic layer 131) is 400 mm in length and 400 mm in width.

[0071] S2. The proton exchange membrane 120 is stacked between the first composite transfer membrane and the second composite transfer membrane. The first catalytic layer 111 and the second catalytic layer 131 are close to the proton exchange membrane 120. The first catalytic layer 111 and the second catalytic layer 131 are aligned. The first support layer 113 and the second support layer 133 are aligned. The first substrate layer 112 and the second substrate layer 132 are aligned. The same end of the first support layer 113 and the second support layer 133 protrudes 200 mm relative to the first substrate layer 112 (second substrate layer 132). The 100 mm protruding protruding proton exchange membrane 120 relative to the first substrate layer 112 (second substrate layer 132) is sandwiched between the first support layer 113 and the second support layer 133 through the adhesive layer and adhered together to form a transfer structure.

[0072] S3 , hot pressing the transfer structure, with the temperature of the hot roller hot pressing being 140° C., the pressure being 2 MPa, and the tension being 12 N, so that the first catalytic layer 111 and the second catalytic layer 131 are transferred onto the proton exchange membrane 120 .

[0073] S4, separating the CCM layer, the first composite transfer film, and the second composite transfer film, and rolling up the CCM layer to obtain a product.

[0074] Example 2

[0075] This embodiment provides a CCM layer, and its transfer method is roughly the same as that of Embodiment 1, except that: the thickness of the support layer (first support layer 113, second support layer 133) is 90 μm; the temperature of the hot roller hot pressing is 180°C, the pressure is 5 MPa, and the tension is 30N.

[0076] Comparative Example 1

[0077] This comparative example provides a CCM layer, which is prepared according to the following transfer method:

[0078] S1. Coat the first catalytic layer corresponding to the anode on the first composite transfer film, and coat the second catalytic layer corresponding to the cathode on the second composite transfer film. The thickness of the first composite transfer film and the second composite transfer film are 60 μm respectively. The first composite transfer film is a first substrate layer and a first support layer composited together. The second composite transfer film is a second substrate layer and a second support layer composited together. The substrate layer (first substrate layer, second substrate layer) is made of polytetrafluoroethylene with a thickness of 30 μm. The support layer (first support layer, second support layer) is made of PET with a thickness of 30 μm. The materials and thickness of the first catalytic layer and the second catalytic layer are the same as those in Example 1.

[0079] S2. A three-layer structure of a first composite transfer membrane, a proton exchange membrane, and a second composite transfer membrane is formed. The first catalytic layer and the second catalytic layer are close to the proton exchange membrane. A traction belt is used to align the three-layer structure. The alignment method is a matching alignment method for a roll-to-roll transfer device.

[0080] S3. The transfer structure is hot pressed, and the temperature of the hot roller hot pressing is 140° C., the pressure is 2 MPa, and the tension is 12 N, so that the catalyst layer is transferred to the proton exchange membrane.

[0081] S4, separating the CCM layer, the first composite transfer film, and the second composite transfer film, and rolling up the CCM layer to obtain a product.

[0082] Comparative Example 2

[0083] This comparative example provides a CCM layer, and its transfer method is roughly the same as that of comparative example 1, except that: the thickness of the first composite transfer film and the second composite transfer film are both 120 μm, the thickness of the substrate layer (first substrate layer, second substrate layer) is 60 μm, and the thickness of the support layer (first support layer, second support layer) is 60 μm.

[0084] The performance tests and evaluations of the coatings (catalytic layers) in the embodiments and comparative examples are as follows:

[0085] 1. Observe whether cracking occurs during coating (catalytic layer);

[0086] 2. Observe whether the transfer coating (catalytic layer) is deformed;

[0087] 3. Measure the alignment accuracy of the coating (catalytic layer);

[0088] 4. The transverse shrinkage rate and longitudinal elongation rate are obtained by measuring the size of the coating (catalytic layer) before and after transfer.

[0089] The test results are shown in Table 1.

[0090] Table 1 Performance results of different products

[0091]

[0092]

[0093] It can be seen from Table 1 that the coating obtained by the transfer method of the embodiment of the present application has high coating quality (the coating does not crack) and high transfer quality (the coating does not deform and the shrinkage rate is controlled), while the transfer method of comparative example 1 cannot guarantee the transfer quality and alignment accuracy, and the transfer method of comparative example 2 cannot guarantee the coating quality and alignment accuracy.

[0094] To sum up, the transfer method of the catalytic layer of the embodiment of the present application can ensure the coating preparation effect of the catalytic layer, and can also improve the strength of the transfer film, reduce the deformation of the catalytic layer after transfer, and at the same time ensure accurate positioning during transfer to improve the transfer quality.

[0095] The above description is only an embodiment of the present application and is not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for transferring a catalytic layer, characterized in that: It includes the following steps: A catalytic layer is coated on the front side of the substrate layer, and a supporting layer is adhered to the back side of the substrate layer to form a composite transfer film; The proton exchange membrane is stacked between two layers of the composite transfer membrane, and the catalytic layer of each layer of the composite transfer membrane is close to the proton exchange membrane to form a transfer structure; Hot pressing the transfer structure to transfer the catalytic layer onto the proton exchange membrane; The substrate layer, the support layer and the proton exchange membrane are separated.

2. The method for transferring the catalyst layer according to claim 1, characterized in that: The support layer is adhered to the back side of the substrate layer by a heat-sensitive adhesive.

3. The method for transferring the catalyst layer according to claim 2, characterized in that: A heat-sensitive adhesive is coated on the front side of the support layer to form a heat-sensitive adhesive layer, and then the front side of the support layer is adhered to the back side of the substrate layer.

4. The method for transferring the catalyst layer according to claim 3, characterized in that: The thickness of the heat-sensitive adhesive layer is 30-60 μm.

5. The method for transferring a catalyst layer according to claim 1, characterized in that: When forming the transfer structure, the same end of the support layer of the two layers of the composite transfer membrane is extended out and adhered to the proton exchange membrane.

6. The method for transferring the catalyst layer according to claim 5, characterized in that: The protruding ends of the two support layers are adhered together by a heat-sensitive adhesive to form the transfer structure.

7. The method for transferring a catalyst layer according to claim 5, characterized in that: The catalytic layer is an intermittent coating formed by intermittent coating, and the protruding ends of the two support layers are adhered together so that the two catalytic layers are aligned.

8. The method for transferring a catalyst layer according to claim 5, characterized in that: The extension length of the support layer relative to the substrate layer is 20-500 mm, the extension length of the proton exchange membrane relative to the substrate layer is 10 mm-100 mm, and the extension length of the proton exchange membrane is smaller than the extension length of the support layer.

9. The method for transferring a catalyst layer according to claim 1, characterized in that: The temperature of the hot pressing is 120-200° C., the pressure is 1-8 MPa, and the tension is 10-50N.

10. The method for transferring a catalyst layer according to claim 1, characterized in that: The material of the substrate layer includes at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene terephthalate, and polybutylene terephthalate, and the thickness of the substrate layer is 30-150 μm; And / or, the material of the support layer includes at least one of polyester, polycarbonate, triacetyl cellulose, polytetrafluoroethylene fabric, cellophane, polyphenylene sulfide, polysulfone, polyether sulfone, and polypropylene, and the thickness of the support layer is 60-160 μm; And / or, the thickness of the catalytic layer is 10-30 μm.

Citation Information

Patent Citations

  • Heat-sensitive pressure-sensitive adhesive composition and pressure-sensitive adhesive sheet

    JP2003138237A

  • Temperature-sensitive adhesive tape

    JP5512143B2

  • Fuel cell membrane electrode and preparation method thereof

    CN113381045A

  • Membrane electrode assembly and preparation method and application thereof

    CN116190732A

  • Device and method for improving heat transfer printing rate of membrane electrode large-area flat plate

    CN117476954A